Possibilities and challenges of the internet of musical things - Carneiro, Gabriel Rodrigues Chaves (2022)
The Internet of Musical Things is a research area that aims to bring Internet of Things connectivity to the field of music and the arts. Altogether with this technology, there is the possibility of connecting different musical things in a concert or artistic creation environment that would allow, for example, the participation of the public in these processes, both in person, through a local network, and remotely, via the Internet. In this work we bring some discussions about IoMusT and also its possibilities and future challenges.